Identification and functional validation of SPON2 as a novel biomarker for the diagnosis and prognosis in hepatocellular carcinoma - He, Wanrong; He, Zehua; Chen, Qingfeng; Lan, Wei; Zhang, Guo (Journal of Gastrointestinal Oncology, 2026)
Background: Hepatocellular carcinoma (HCC) is a major global health burden, with persistently low 5-year survival rates. The major clinical challenge in HCC lies in the lack of accurate biomarkers for early detection, prognostic evaluation, and prediction of tumor aggressiveness. This study aimed to identify reliable biomarkers for HCC diagnosis and outcome prediction, and to elucidate their functional relevance in tumor progression.Methods: Transcriptomic profiles of HCC and adjacent normal tissues, along with single-cell RNA sequencing (scRNA-seq) data from six HCC patients, were obtained from public databases. The differentially expressed genes (DEGs) were identified and functionally annotated. HCC tumor cell-specific genes were determined using the “FindAllMarkers” function. Genes that were upregulated in both HCC tissues and tumor cells were considered candidate biomarkers. Western blotting and quantitative reverse transcription polymerase chain reaction (qRT-PCR) were used to assess spondin-2 (SPON2) and WNT-related gene expression. Cell counting kit-8 (CCK-8), 5-ethynyl-2'-deoxyuridine (EdU), as well as colony formation assays evaluated cell proliferation. Additionally, wound healing and transwell assays assessed migration and invasion capacities.Results: Integration of bulk transcriptomic and scRNA-seq datasets identified SPON2 as an HCC-specific biomarker. SPON2 showed favorable diagnostic accuracy in distinguishing HCC patients from healthy controls across four independent cohorts, and its elevated expression was linked to poor overall survival (OS) and increased metastatic potential. At the single-cell level, SPON2+ tumor cells showed higher invasion and migration scores. Functional assays confirmed that SPON2 promoted the proliferative, migrative, and invasive capacities of HCC cells in vitro. Moreover, SPON2 expression exhibited a robust positive correlation with the activation of WNT signaling pathway; while SPON2 knockdown suppressed WNT-related protein expression.Conclusions: Through integrative transcriptomic and single-cell analyses, SPON2 was identified as a robust HCC biomarker, aberrantly upregulated in HCC tissues and tumor cells, and predictive of shorter OS and enhanced metastatic potential. By activating the WNT signaling pathway, SPON2 enhances the proliferative, migrative, and invasive capacities of HCC cells, underscoring its pivotal role in tumor aggressiveness and providing insights into novel diagnostic and prognostic targets for HCC management.